Performing new media, 1890-1915 - Askari, Kaveh; Curtis, Scott; Gray, Frank; Pelletier, Louis; Williams, Tami, 1970-; Yumibe, Joshua (New Barnet, Herts : John Libbey Publishing Ltd., 2015)
In the years before the First World War, showmen, entrepreneurs, educators, and scientists used magic lanterns and cinematographs in many contexts and many venues. To employ these silent screen technologies to deliver diverse and complex programs usually demanded audio accompaniment, creating a performance of both sound and image. These shows might include live music, song, lectures, narration, and synchronized sound effects provided by any available party--projectionist, local talent, accompanist or backstage crew--and would often borrow techniques from shadow plays and tableaux vivants. The performances were not immune to the influence of social and cultural forces, such as censorship or reform movements. This collection of essays considers the ways in which different visual practices carried out at the turn of the 20th century shaped performances on and beside the screen.
Part I. Performing on the screen : actors and personalities -- Lois Weber at Rex : performing femininity across media / Shelley Stamp -- Diva intermedial : Lyda Borelli between art, photography, theatre and cinema / Ivo Blom -- Why sue "Little Mary?" : how Independent Moving Pictures Company of America v Gladys Smith and Owen Moore (1911) defined celebrity and professionalism for film actors / Leslie Midkiff DeBauche -- Camera distance and acting in the Griffith Biography / Charles O'Brien -- Performance times : the lightning cartoon and the emergence of animation / Malcolm Cook -- La transparence du Fregoligraph en question / Frédéric Tabet -- In the flesh : personal appearances and the picture personality in Britain / Chris O'Rourke -- Performers : now synchronised on screen / Ian Christie -- Part II. Performing beside the screen : narrators, showmen, and musicians -- Missing believed lost : the film narrator, then and now / Martin Loiperdinger -- Standards of practice in transition : the showmanship of Jasper Redfern as it emerged / Peter Walsh -- Showmanship skills and the changing role of the exhibitor in 1910s Scotland / María Antonia Vélez-Serna -- Showing film in winter (1904-1906) : Alberts Frères' film galas in Dutch multi-purpose buildings / Ansje van Beusekom -- Performing new media and the creation of national identity : Kräusslich and Köpke in Norway before 1910 / Gunnar Iversen -- Music programming and the formation of Swedish cinema culture / Christopher Natzén -- "Marvelous and fascinating" : L. Frank Baum's Fairylogue and radio-plays (1908) / Artemis Willis -- The multiple media lecture : Racing with death in Antarctic blizzards (1915) / Gregory A. Waller -- Part III. Performing with the screen : audiences, educators and officials -- Kinoreformbewegung revisited : performing the cinematograph as a pedagogical tool / Frank Kessler and Sabine Lenk -- Health on display : the Panama-Pacific International Exposition as sanitary venue / Marina Dahlquist -- Lyrical education : music and colour in early non-fiction film / Jennifer Peterson -- "Offensive and riotous behaviour"? Performing the role of an audience in Irish cinema of the mid-1910s / Denis Condon -- Tango mad and affected by cinematographitis : rhythmic "contagions" between screens and audiences in the 1910s / Kristina Köhler -- Part IV. Intermedial performance -- Screening sensations and live performance : the creative blending of traditional and new projected media at the start of the twentieth century / Ludwig Maria Vogl-Bienek -- Le spectacle de lanterne magique considèrè sous l'angle de la conférence : quelques traces écrites d'une performance orale / Alain Boillat -- Getting to know the Dutch : magic lantern slides as traces of intermedial performance practices / Sarah Dellmann -- 20 minutes or less : short-form film-and-theatre hybrids : skits, sketches, playlets, and acts in vaudeville, variety, revues, &c. / Gwendolyn Waltz -- Between Karagöz and cinema : connectivity, mobility, collectivity / Canan Balan -- Entre nouveauté et continuité : le spectacle cinématographique serait-il une émergence des ombres françaises? / Thierry Lecointe -- "Performed live and talking. No kinematograph" : amateur performances of Tableaux vivants and local film exhibition in Germany around 1900 / Daniel Wiegand -- Performing painting : projected images as living pictures / Valentine Robert -- Colour as performance in visual music, film tinting and digital painting / Joshua Yumibe -- Coda -- Early cinema today and its "digital performance" : the re-discovery of The soldier's courtship (1896) / Franziska Heller.
28 essays in English and 3 in French.
Vendor-supplied metadata.
JSTOR
Keywords: Silent films -- History; Motion pictures and theater -- History; Art; Art; Motion Pictures as Topic; Films muets -- Histoire; Cinéma et théâtre -- Histoire; Art; PERFORMING ARTS -- Reference; Art; Motion pictures and theater; Silent films; History